2011
DOI: 10.4012/dmj.2010-131
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization and bond strengths between Ti-20Cr-1X alloys and low-fusing porcelain

Abstract: This study evaluated the bond strengths between experimental Ti-20Cr-1X (X=Nb, Mo, Fe, Zr) alloys and porcelain (Duceratin). The results of this bond strength testing indicated that all the Ti-20Cr-1X alloys exceeded the lower limit value in the ISO 9693 standard for the 3-point bending test (25 MPa), and were all higher than that of commercially pure titanium (c.p. Ti). The coefficient of thermal expansion (CTE) values of all Ti-20Cr-1X alloys were higher than that of c.p. Ti, and this result of a closer matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…2). This result points to lower bond strength and parallels earlier findings by Ho et al and Wu et al [13,16]. Observation with an SEM/EDS showed that after the bond strength test, the Ti-5Cr-9Mo alloy had more adherent porcelain on its surface than the c.p.…”
Section: Sem Observationsupporting
confidence: 92%
See 3 more Smart Citations
“…2). This result points to lower bond strength and parallels earlier findings by Ho et al and Wu et al [13,16]. Observation with an SEM/EDS showed that after the bond strength test, the Ti-5Cr-9Mo alloy had more adherent porcelain on its surface than the c.p.…”
Section: Sem Observationsupporting
confidence: 92%
“…Ho et al and Wu et al reported that the addition of Cr and Mo to Ti alloys could result in high bond strength between metal and porcelain [13,16]. Both research teams found a high percentage of Mo within the oxide layer of the Ti-5Cr alloy, and this Mo content may be essential in establishing a chemical bond between porcelain and alloy.…”
Section: Bond Strengthmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the use of TIG welding in dentistry is uncommon, some studies show the superiority of this technique compared to conventional brazing 18,19 . Several studies have evaluated the bond strength of porcelain in different alloys 7,[20][21][22] . However, few studies have evaluated the bond strength of ceramics in regard with TIG welding or brazing.…”
Section: Introductionmentioning
confidence: 99%